Vidalian traces: Genre de vie, culture and democracy - Entrikin, J. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l’Université Laval, 2021)
Modern geographers have tended to reimagine their discipline with very little acknowledgement of a disciplinary past. The relative absence of reference to the work of Paul Vidal de la Blache in the current geographical literature illustrates this disciplinary amnesia. In Anglophone literature, Vidal is recognized for his impact in other disciplines. In geography, his work has moved from that of a classic that is reread by succeeding generations to being part of the acknowledged but largely unread geographical canon. In part this is a consequence of the narrow interpretation that links Vidal’s legacy to the changing fortunes of Anglo-American regional geography. The recent reconsideration of Vidal’s last publication, La France de L’Est (Lorraine-Alsace), has suggested a more multidimensional Vidal. These rereadings have concentrated on political geography. However, he also engaged themes related to those found in the writings of his contemporaries, Durkheim and Dewey. Durkheim and Dewey have been common reference points in current scholarship in ways that have thus far eluded Vidal.